1986
DOI: 10.1113/jphysiol.1986.sp015960
|View full text |Cite
|
Sign up to set email alerts
|

The release of histamine by parasympathetic stimulation in guinea‐pig auricle and rat ileum.

Abstract: SUMMARY1. Two preparations, a segment of rat ileum and the vagally innerved guinea-pig auricles, have been used in an analysis of the responses to vagal or to electrical field stimulation.2. The responses to parasympathetic stimulation were depressed by atropine and by tetrodotoxin, and potentiated by eserine.3. Supramaximal stimulation (10-20 Hz) resulted in increased release of acetylcholine and histamine, both in rat ileum and guinea-pig auricles.4. The release of histamine after parasympathetic stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…It has been reported that histamine is released from mast cells in the intestinal wall of some species during electrical stimulation and hence, it may participate in the regulation of motor and secretory functions (Sacchi et al 1986). For example, the H 3 receptor antagonists thioperamide and impromidine have been reported to enhance electrically-evoked acetylcholine release in the guinea-pig ileum ).…”
Section: Functional Studiesmentioning
confidence: 99%
“…It has been reported that histamine is released from mast cells in the intestinal wall of some species during electrical stimulation and hence, it may participate in the regulation of motor and secretory functions (Sacchi et al 1986). For example, the H 3 receptor antagonists thioperamide and impromidine have been reported to enhance electrically-evoked acetylcholine release in the guinea-pig ileum ).…”
Section: Functional Studiesmentioning
confidence: 99%
“…The different grey levels were obviously expressed in lower percentage values. The analysis of the image plan was carried out as previously described [33,34]. The program allowed for statistical and graphic elaboration of data.…”
Section: Computer-aided Analysis Of Mast Cell Metachromasiamentioning
confidence: 99%
“…Although we activated mast cells with an immunological stimulus in this study, a variety of endogenous neurotransmitters and neuropeptides can release histamine from mast cells in other tissues (Foreman & Jordan, 1983;Bani-Sacchi, Barattini, Bianchi, Blandina, Brunelleschi, Fantozzi, Mannaioni & Masini, 1986;Leff, Stimler, Muhoz, Shioya, Tallet & Dame, 1986;Bienenstock, Tomioka, Matsuda, Stead, Quinonez, Simon, Coughlin & Denburg, 1987). The ability of these substances to act as mast cell secretagogues is dependent on the source of the mast cells, since considerable heterogeneity exists between mast cells from different tissues (Befus, Bienenstock & Denburg, 1986).…”
Section: Endogenous Histamine Excites Neuronesmentioning
confidence: 99%